PENERAPAN MODEL PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA KELAS VII SMP NEGERI 9 LUBUKLINGGAU - Febriyanti, Aprilliana; sukasno, sukasno; Mandasari, Novianti (Jurnal Pendidikan Matematika Undiksha, 2020)
ABSTRACTThis study is entitled "The Implementation of Problem Solving Model to Improve Mathematical Problem Solving Ability of Class VII Students of SMP Negeri 9 Lubuklinggau". This study aims to determine the increase in students' problem solving abilities in learning mathematics after being applied using a problem solving model. The type of research used is Pre Experimental Design. The population of all VII grade students of SMP Negeri 9 Lubuklinggau totaling 248 students and as a sample of class VII.5 with 32 students, the sample was taken randomly. Data collection was carried out using test techniques. The collected data were analyzed using t-test at a significant level = 0.05. Based on the results of the final test data analysis it can be concluded that. There is an increase in the ability to solve math problems of VII graders of SMP Negeri 9 Lubuklinggau after applying the problem solving model. The average value of students' mathematical problem solving abilities is 28.24.